Learning to teach German: Blended-learning training programmes for future German language teachers. - Costa, Marcella; Hausner, Alexandra; Katelhoen, Peggy (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2014)
Learning to teach German: Blended-learning training programmes for future German language teachers. This article discusses the features of the teacher training course for German teachers held at the University of Turin during the academic year 2012/13. Starting from the description of the framework agreement between our Department and the Goethe Institut Italien, we will then describe the theoretical framework of the new teacher training program Deutsch Lehren Lernen (DLL) as well as its innovative methodological tools and show how the DLL-modules have been implemented in our specific context. The course takes into account the most recent developments in the teaching of German as a foreign language and it is characterized by an innovative approach which includes blended learning and an overall division into modules. The general conceptual and theoretical bases of the course will be presented, with a discussion of its use in specific conditions and needs of Italian foreign language teachers. The article will conclude with an evaluation of the course and proposals for future training of foreign language teachers in Italy.